Circularly polarized luminescence from AIEgens - Song, Fengyan; Zhao, Zheng; Liu, Zhiyang; Lam, Jacky W. Y; Tang, Ben Zhong (Journal of materials chemistry. C, Materials for optical and electronic devices, 2020)
Circularly polarized luminescence (CPL) based on aggregation-induced emission luminogens (AIEgens) has received increasing attention owing to the increase of applications to generate CPL devices and biologically active probes. CPL-active materials fabricated from AIEgens exhibit higher photoluminescence quantum yields and larger dissymmetry factors in the solid state in comparison with single molecules in solution. We called the phenomenon of enhanced CPL in an aggregated state aggregation-induced circularly polarized luminescence (AICPL). This review highlights recent research in the CPL generation of AIEgens from (macro)molecular luminogens and supramolecular assemblies based on the AIE mechanism of restriction of intramolecular motion. In addition, some cases in which CPL-active AIEgens have enabled advancement in stimulus response materials and application in CPL devices, especially circularly polarized electroluminescence. Thus, CPL-active AIEgens are highly promising candidates for a wide range of technologically oriented multidisciplinary fields. This work systematically summarizes recent advances in circularly polarized luminescence (CPL) based on aggregation-induced emission luminogens (AIEgens).